2022
DOI: 10.3389/fpubh.2022.825988
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Cognitive Dysfunction Accommodation Strategies Into Behavioral Interventions for Persons on Medication for Opioid Use Disorder

Abstract: BackgroundCognitive dysfunction is disproportionately prevalent among persons with opioid use disorder (OUD). Specific domains of cognitive dysfunction (attention, executive functioning, memory, and information processing) may significantly impede treatment outcomes among patients on medication for OUD (MOUD). This limits patient's ability to learn, retain, and apply information conveyed in behavioral intervention sessions. Evidence-based accommodation strategies have been integrated into behavioral interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Strategies on how to compensate for this cognitive deficit during behaviour interventions in these patients include having structure and consistency, simple and clear language, using a range of modalities, memory aids e.g. reminders and frequent assessments with immediate feedback during the intervention [ 64 , 67 ]. These point to potential barriers that need to be considered during future implementation of a text-based intervention in this study population.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies on how to compensate for this cognitive deficit during behaviour interventions in these patients include having structure and consistency, simple and clear language, using a range of modalities, memory aids e.g. reminders and frequent assessments with immediate feedback during the intervention [ 64 , 67 ]. These point to potential barriers that need to be considered during future implementation of a text-based intervention in this study population.…”
Section: Discussionmentioning
confidence: 99%
“…Based on research in other populations, a number of potential accommodation strategies were theorized to compensate the particular domains of cognitive dysfunction that are often present in persons on MOUD [ 14 ]. We presented this foundation of research to drug treatment providers and patients on MOUD to inform the current study and narrow down which specific strategies may demonstrate the greatest efficacy in a drug treatment setting [ 19 ]. The accommodation strategies examined in this pilot study included strategies shown to compensate the specific domains of cognitive dysfunction that are often present among persons on MOUD (i.e., attention, executive functioning, memory, information processing), and that were most frequently endorsed by key informants in focus group research [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…We presented this foundation of research to drug treatment providers and patients on MOUD to inform the current study and narrow down which specific strategies may demonstrate the greatest efficacy in a drug treatment setting [ 19 ]. The accommodation strategies examined in this pilot study included strategies shown to compensate the specific domains of cognitive dysfunction that are often present among persons on MOUD (i.e., attention, executive functioning, memory, information processing), and that were most frequently endorsed by key informants in focus group research [ 19 ]. Outcomes from this study indicate that the accommodation strategies improved participants’ ability to learn and retain intervention content, and to accurately utilize the recalled HIV risk reduction skills over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary activity of the preparation phase is developing a detailed conceptual model that expresses how each component is expected to impact the process—in this case, the uptake of primary HIV prevention behaviours. The preparation phase was completed in our preliminary work,9–12 29 36 which resulted in the identification of four compensatory components (ie, attention, executive functioning, memory and information processing) that show promise in terms of enhancing participants’ ability to process and use primary HIV prevention intervention information13 (table 1).…”
Section: Methods and Analysismentioning
confidence: 99%